Faster parameterized algorithm for Bicluster Editing - Tsur, Dekel (Information processing letters, 2021)
•We give an O⁎(2.636k)-time algorithm for Bicluster Editing.•Our algorithm is faster than previous algorithms for this problem.•The algorithm uses branching rules that branch on every minimal editing set of some induced subgraph of the input graph. In the Bicluster Editing problem the input is a bipartite graph G and an integer k, and the goal is to decide whether G can be transformed into a bicluster graph by adding and removing at most k edges. In this paper we give an algorithm for Bicluster Editing whose running time is O⁎(2.636k).